External Sector Report, July 2019 : The Dynamics of External Adjustment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
The IMF's 2019 External Sector Report shows that global current account balances stand at about 3 percent of global GDP. Of this, about 35-45 percent are now deemed excessive. Meanwhile, net credit and debtor positions are at historical peaks and about four times larger than in the early 1990s. Short-term financing risks from the current configuration of external imbalances are generally contained, as debtor positions are concentrated in reserve-currency-issuing advanced economies. An intensification of trade tensions or a disorderly Brexit outcome-with further repercussions for global growth and risk aversion-could, however, affect other economies that are highly dependent on foreign demand and external financing. With output near potential in most systemic economies, a well-calibrated macroeconomic and structural policy mix is necessary to support rebalancing. Recent trade policy actions are weighing on global trade flows, investment, and growth, including through confidence effects and the disruption of global supply chains, with no discernible impact on external imbalances thus far.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet